HOW PRODUCT DEVELOPMENT, ADVERTISING, AND SERVICE QUALITY INFLUENCE CUSTOMERS SAVING DECISION CASE STUDY ON STATED-OWNED BANKS IN JAKARTA - Novela, Selly; Hanafie, Steffi Mutia Irenda (SEEIJ (Social Economics and Ecology International Journal), 2017)
The competition between Banks in Indonesia required the existence of a marketing strategy for appropriate banking products and services offered on the state-owned bank in Indonesia, including in Jakarta. This study aims to determine whether there is influence between variable Product Development, Advertising and Service Quality, to Saving Decision in State-Owned Bank in Jakarta. Methods of data collection using a survey distributed to 127 customers. The research method used quantitative descriptive analysis and method of data analysis used in this research is multiple regressions. The results of this study, shows that Product Development, Advertising and Service Quality has an influence on Customers Saving Decision at State-Owned Banks in Jakarta.